Bacteriocin Typing of Vibrio cholerae - Chakrabarty, A. N. (1970)
Bacteriocins of Vibrio cholerae have been demonstrated against enterobacterial and vibrio indicator organisms by conventional techniques. Abundant bacteriocin production took place on casein hydrolysate-yeast extract, tryptic soy, digest broth, proteose-peptone, and neopeptone agars. Essential factors were a citrate-phosphate buffer concentration of 0.5 to 0.7%, at pH 7.5 to 7.6, and cold shock. Thermal treatment of indicator organisms at 45 C for 12 min increased the percentage of typable strains. The bacteriocins of V. cholerae appeared to be powerful diffusible bactericidal agents. By using 8 indicator strains, 11 bacteriocin types have been recognized among 425 strains, of which 87% are typable at present.